2017
DOI: 10.1016/j.neuroscience.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Rapid stimulation of sodium intake combining aldosterone into the 4th ventricle and the blockade of the lateral parabrachial nucleus

Abstract: Chronic infusion of aldosterone into the 4th ventricle (4th V) induces robust daily sodium intake, whereas acute injection of aldosterone into the 4th V produces no sodium intake. The inhibitory mechanism of the lateral parabrachial nucleus (LPBN) restrains sodium intake induced by different natriorexigenic stimuli and might affect the acute response to aldosterone into the 4th V. In the present study, 1.8% NaCl and water intake was tested in rats treated with acute injections of aldosterone into the 4th V com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Electrolyte homeostasis necessarily involves the regulation of both sodium excretion and sodium intake. Dietary sodium deprivation elicits a strong salt appetite in rats, 86 as does bilateral adrenalectomy, 87,88 aldosterone via its actions on the brain, 89,90 and hypovolaemic stimuli. [91][92][93] The AV3V region is strongly implicated in salt appetite, in part via central angiotensin II pathways from the subfornical organ.…”
Section: Salt Appetitementioning
confidence: 99%
“…Electrolyte homeostasis necessarily involves the regulation of both sodium excretion and sodium intake. Dietary sodium deprivation elicits a strong salt appetite in rats, 86 as does bilateral adrenalectomy, 87,88 aldosterone via its actions on the brain, 89,90 and hypovolaemic stimuli. [91][92][93] The AV3V region is strongly implicated in salt appetite, in part via central angiotensin II pathways from the subfornical organ.…”
Section: Salt Appetitementioning
confidence: 99%
“…As the critical component of the amygdaloid nucleus, the CeA receives ascending fiber projections of many nuclei in the brainstem, while it emits fiber projections to the dorsal nucleus of the vagus nerve, solitary nucleus, periaqueductal gray matter, and reticular nuclei of the pons. Recent studies have demonstrated that a close fiber link exists between the CeA and a number of regions of the brain associated with sodium intake regulation, such as signals from the HSD2 neuron (Geerling et al., 2006 ; Resch et al., 2017 ) in the solitary nucleus, relayed by the parabrachial nucleus, projected upward to the lateral CeA, and then projected directly by the medial CeA to the HSD2 neuron, which may be an important neural loop where the CeA participates in the regulation of sodium intake (Gasparini et al., 2017 ). In addition, the CeA has a fibrous connection with the nucleus of the reward system and emits fiber projections to neuroendocrine nuclei, such as the chamber nucleus.…”
Section: Discussionmentioning
confidence: 99%